Are Third-Party Fundamental Valuations Relevant in Public Company Takeovers? - Shaffer, Matthew (Management Science, 2023)
In U.S. mergers and acquisitions, target directors are required to consider third-party financial valuations, summarized in a “fairness opinion” before accepting a takeover offer. Critics argue (1) that these valuations are not relevant for public companies, which can assess the desirability of the deal based on the market premium, and (2) that the investment bank providers cater to management by “rationalizing” the deal price rather than providing an independent valuation check. I find that fairness valuations can provide valid information about the target’s value, incremental to its predeal stock price. They can impound expected transaction synergies, unravel rumor-driven stock price runups, and may signal ex ante fundamental mispricing. I also find evidence of the alleged catering, which I distinguish from “legitimate” valuation disagreements. This suggests that third-party fundamental valuation could play a useful role in the governance of public company takeovers, but there are flaws in its current implementation. This paper was accepted by Brian Bushee, accounting. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.4959 .